Theorizing the Grey Area between Legitimacy and Illegitimacy - Siraz, Sonia; Claes, Björn; Castro, Julio de; Vaara, Eero; Castro, Julio de (Journal of Management, 2023)
Despite a proliferation of research on legitimacy,the ‘grey area’ that lies between legitimacy and illegitimacy remains undertheorized. Responding to calls for further research,we clarify the construct of legitimacy and extend legitimacy theory by providing a conceptual framework for analyzing the legitimacy-illegitimacy continuum. First,we propose three novel legitimacy states between legitimacy and illegitimacy – conditional legitimacy,unknown legitimacy,and conditional illegitimacy – and elaborate on the distinct qualitative characteristics of the five legitimacy states. Second,we offer a model of the dynamics of legitimacy state change and the (in)stability of the issue-specific reference framework that is used to judge them. Third,we explain how our legitimacy states bridge the research streams on legitimacy judgment formation and legitimation strategies. By doing so,we integrate these research streams and enumerate discursive strategies for each state. Our article contributes to a more robust understanding of both how legitimacy states can be conceptualized and analyzed in future research and how they can be dealt with in managerial practice. © 2022 The Authors. Journal of Management Studies published by Society for the Advancement of Management Studies and John Wiley & Sons Ltd.
Keywords: Illegitimacy; Legitimacy; Legitimacy-illegitimacy continuum; Legitimation strategy; Polarization; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 10 - Reducción de las desigualdades; ODS 12 - Producción y consumo responsables; ODS 16 - Paz, justicia e instituciones sólidas